PENGARUH PERJUMPAAN LINTAS IMAN TERHADAP SIKAP TOLERANSI ANTAR UMAT BERAGAMA PADA MAHASISWA STFT INTIM MAKASSAR - Aulia, Guruh Ryan; Muin, Muh Raihan Gymnastiar (UIN Sumatera Utara Medan, 2025)
This study aims to examine the influence of interfaith encounters on religious tolerance among students of STFT INTIM Makassar. Using a quantitative approach, data were collected through questionnaires distributed to 42 students who had participated in interfaith activities. Regression analysis results show that interfaith encounters contribute 13.3% to the development of tolerant attitudes. The findings indicate a positive and significant relationship between the intensity of participation in interfaith activities and students' tolerance toward religious diversity. Thus, interfaith engagement proves to be an effective means of fostering mutual respect and strengthening relationships among adherents of different religions. This study contributes significantly to the development of educational programs that promote the values of pluralism, multiculturalism, and social harmony.